Long-term stroke incidence in proximal thoracic aorta aneurysm survivors. Issue 4 (June 2020) - Hsu, Jin-Yi; Su, Yuan-Chih; Wang, Jen-Hung; Tee, Boon Lead
Background: Aneurysm of proximal thoracic aorta (pTAA) is an often indolent, yet fatal disease. Although advancements in aneurysmal repair techniques have increased long-term survival rates, studies have proven that there are increases in perioperative risk for stroke incidence after pTAA surgery. Conversely, there is little evidence regarding the long-term stroke incidence in pTAA individuals, which strongly influences the morbidity, mortality, and usage of antithrombotic agents. Methods: Using the Taiwan National Health Insurance Research Database, a nationwide population-based cohort, we recruited 3013 pTAA survivors hospitalized from 1 January 2000 to 31 December 2012. To ensure study cohort quality, only patients aged 20 years and above who underwent aneurysmal repair surgery are included. The control cohort is identified by matching background features (comorbidities, age, gender) at a 1:4 ratio through the use of frequency matching. The primary outcomes include incidence of ischemic stroke and intracranial hemorrhage one month after aneurysmal repair surgery. Results: The mortality of pTAA survivors is nearly twice of the matched controls despite aneurysmal repair (28.5 % vs. 15.2%, p < 0.001). Long-term follow-up of participants indicated that pTAA survivors had a higher risk for hemorrhage stroke (adjusted hazard ratio (aHR): 1.93; 95% confidence interval (CI): 1.47–2.53), but no significant increase in risk for ischemic stroke (aHR: 1.07; 95% CI: 0.92–1.25). Hemorrhagic stroke occurrence was found to be associated with age and diabetes mellitus. Comparison on hemorrhagic stroke subtypes between study and matched cohorts showed no statistical differences in intracerebral hemorrhage and subarachnoid hemorrhage. Conclusions: Despite the advancement of aneurysmal repair surgery, this study suggests that pTAA patients may still face an increased risk of hemorrhage stroke. Further investigation is warranted to provide better long-term care for the pTAA population.